Fuel of the past, present, and future - Scheel, John Alfred (My University, 1894)
Introduction: Importance of fuel question; early condition of man and surroundings; first use of fuel, —steps taken in the use of fuel. Periods in the use of fuel; —prior to coal; —Era of coal.—what this use of coal has done for progress,—will there be an age of gas?—durability of gas as fuel. Our fuel supply, —coal, —wood, —gas and petroleum—possible exhaustion, —what exhaustion would mean. Smoke consumers, —smoke nuisance, —waste of energy through unburned gases, Sicmins gas producer compared to coal stove. – combustion of sulphur in coal— products formed, effects on vegetable and animal life. Conversion of solid fuels to gas for use as a fuel; —desirability of gas as a fuel, is the sclume possible and practicable,—economy of gas as a fuel and other desirable features. Petroleum as a fuel, water ditto, artificial fuels, value of different fuels, appliances for consumption of fuel, need of further improvements in appliances.
Citation: Scheel, John Alfred. Fuel of the past, present, and future. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Fuel; Coal; Pollution; Gas; Desirability; Geology; Theses; Manuscripts (documents)